Pressure–impulse diagrams for elastoplastic beams subjected to pulse-pressure loading. (15th March 2019) - Yuan, Ye; Zhu, Ling; Bai, Xueyu; Yu, T.X.; Li, Yibing; Tan, P.J.
Abstract: Pressure–impulse (or p − I ) diagrams are developed for fully-clamped elastic-plastic beams subjected to pulse-pressure loading with varying degree of negative phase. Unlike traditional p − I diagrams, the loading parameter space are instead divided into r e ´ gimes, corresponding to the three modes of deformation (I, II and III) observed in blast experiments. The effects of pulse shape, beam aspect ratio and negative phase loading on the isodamage curves that delineate the different r e ´ gimes are investigated. In addition, it is further demonstrated that contour lines of structural performance (maximum deflection, total work done, partitioned energy and saturated) can also be incorporated into the non-dimensionalised pressure-impulse space to provide further information for the design, and assessment, of elastic-plastic beams to blast loading.